Analysis Of Quality Control In The Production Process Of Coconut Sugar Organic Ants In Cv. Hugo Innovation, Kebasen District, Banyumas Regency, Central Java - Wulandari, Elsa; Novitasari, Dian (Jenderal Soedirman University, 2022)
Banyumas ranks second in Central Java as the largest producer of coconut plants. The area of land planted with coconut in Banyumas Regency reaches 5,111.49 ha, with the number of coconut trees being 638,936 trees (Banyumas Regency Agriculture & Food Security Agency, 2020). In addition to the flesh, coconut sap can also be used by processing it into coconut sugar. One of the diversified products from coconut sugar is organic coconut sugar. Banyumas Regency encourages the production of organic ant coconut sugar, because of its many advantages, namely the higher selling price, which is up to Rp. 10,000. The water content in organic coconut sugar is lower and the shelf life is longer than coconut sugar. One company that produces organic palm sugar, namely CV. Hugo Innovations. CV. Hugo Innovation is an organic coconut sugar production company, which is located in Tumiyang Village, Kebasen District, Banyumas. CV. Hugo Innovation works closely with local farmers and has an Internal Control System Team of 150 people, 550 farmers and a production capacity of 100 tons/month. The post-harvest processing of coconut sap into organic ant coconut sugar often experiences defects. The type of defect in the coconut sugar product is dark brown with a total damage of 87.3, high humidity 26.25, and coarse grain 70kg in 20 days of observation, namely from October 24, 2021 to November 12, 2021. Based on the analysis of the fishbone diagram the factors Factors that cause damage to coconut sugar are raw materials, labor, machinery and equipment. Strategies for controlling and improving the quality of organic coconut sugar in CV. Hugo Innovation by holding outreach on SOPs, increasing supervision by ICS, using freshly harvested coconut juice, checking pH values before use, ensuring clean juice filtration results, using modern technology in cooking such as ant sugar machines.Keywords: CV. Hugo Innovation, organic coconut sugar, coconut, coconut sap, quality control.